Focusing events and the covid-19 pandemic: The emergency basic income on the brazilian agenda - Brasil, Felipe Gonçalves; Capella, Ana Cláudia Niedhardt [UNESP]; Ferreira, Leandro Teodoro (FapUNIFESP (SciELO), 2021)
Observing and analyzing the causes, effects, and multiple economic, social, and health consequences of the COVID-19 pandemic have been essential to understand this worldwide phenomenon and find solutions that minimize the impacts on peoples’ lives. This article aims to understand the rise of the emergency basic income as a viable policy to tackle the pandemic in Brazil. Based on the agenda-setting literature, specifically on the concept of focusing events, we present a brief history of cash transfer and poverty reduction policies, as well as the actors involved. The study discusses the changes, adaptations, and solutions proposed during the formulation of the emergency basic income as a policy to be considered and effectively adopted in this specific moment of crisis.
Eventos focales y la pandemia de covid-19: La renta básica de emergencia en la agenda del gobierno brasileño
Eventos focalizadores e a pandemia da covid-19: A renda básica emergencial na agenda governamental brasileira
Keywords: Agenda-setting; Basic income; COVID-19; Emergency benefit; Focusing events